External validation of the HIT Expert Probability (HEP) score - Joseph, Lee; Gomes, Marcelo P. V.; Al Solaiman, Firas; Miro-Casas, Elisabet; St John, Julie; Ozaki, Asuka; Raju, Manjunath; Dhariwal, Manoj; Kim, Esther S. H. (Thrombosis and Haemostasis, 2015)
The diagnosis of heparin-induced thrombocytopenia (HIT) can be challenging. The HIT Expert Probability (HEP) Score has recently been proposed to aid in the diagnosis of HIT. We sought to externally and prospectively validate the HEP score. We prospectively assessed pretest probability of HIT for 51 consecutive patients referred to our Consultative Service for evaluation of possible HIT between August 1, 2012 and February 1, 2013. Two Vascular Medicine fellows independently applied the 4T and HEP scores for each patient. Two independent HIT expert adjudicators rendered a diagnosis of HIT likely or unlikely. The median (interquartile range) of 4T and HEP scores were 4.5 (3.0, 6.0) and 5 (3.0, 8.5), respectively. There were no significant differences between area under receiver-operating characteristic curves of 4T and HEP scores against the gold standard, confirmed HIT [defined as positive serotonin release assay and positive anti-PF4/heparin ELISA] (0.74 vs 0.73, p = 0.97). HEP score ≥ 2 was 100 % sensitive and 16 % specific for determining the presence of confirmed HIT while a 4T score > 3 was 93 % sensitive and 35 % specific. In conclusion, the HEP and 4T scores are excellent screening pretest probability models for HIT, however, in this prospective validation study, test characteristics for the diagnosis of HIT based on confirmatory laboratory testing and expert opinion are similar. Given the complexity of the HEP scoring model compared to that of the 4T score, further validation of the HEP score is warranted prior to widespread clinical acceptance.
Keywords: Heparins; thrombocytopenia; thrombosis